PENGARUH CITRA KOPERASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI : PENGARUH CITRA KOPERASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI - Gunawan, Ardi; Purwanto, Kelik (Perkumpulan Doktor Indonesia Maju, 2023)
The image of the cooperative influences the participation of cooperative members through satisfaction. In other words, a cooperative that has a good image is shown by a positive perception of cooperative members as customers and will feel satisfied thereby increasing the participation of members. The purpose of this study was to determine and examine the effect of the image of the cooperative on the satisfaction of the members of the Koperasi Sawit Harapan Makmur Unit II Sungai Ipuh. This study consists of 2 types of variables, namely, the independent variable (free) which includes the image of the cooperative (X1) and the quality of service (X2), as well as the dependent variable (dependent), namely member satisfaction (Y). The instrument used in this research was a questionnaire or questionnaire that was made by the researcher. Based on the data obtained from this study and the results of the analysis that has been carried out, there is a positive and significant influence of the cooperative image variable on the satisfaction variable of the members of the Sawit Harapan Makmur Unit II Sungai Ipuh Cooperative.